Target engagement: shining a light - Huber, K (Springer Nature, 2017)
The ability to measure the binding of a compound to its intended target in live cells or tissue is a critical parameter for drug discovery. A new method using polarized light microscopy adds to the current toolbox by enabling monitoring of target engagement in vitro and in vivo at single-cell resolution.